Corporate Job Ladders in Europe: Wage Premia for University vs. High School Level Positions - Erik Mellander; Per Skedinger (The Research Institute of Industrial Economics (IUI), 1998)
Investment in human capital is a central issue in the literature on economic growth. The purpose of this study is to shed light on the economic incentives for investment in university education across countries. An empirical investigation of earnings for private-sector engineers and business administrators in seven European countries - Belgium, Denmark, France, Germany, Italy, Sweden and the United Kingdom - is presented. The analysis is based on a large micro-data set that is ideally suited for international comparisons. It contains information on earnings, age, occupation, responsibility level, industry and firm size. Standardized wage premia for university vs. high school level positions are computed for each country and field of work. The results indicate that the wage premia are higher for business administrators than for engineers in all the countries considered and that the premia for engineers are remarkably similar across countries. Aggregation over fields of work, which is not uncommon in studies on the returns to education, therefore seems to be questionable practice when comparing the returns in different countries.
Keywords: J31; J44; 330; Returns to education; Company wage policies; Bildungsertrag; Akademiker; Ingenieure; Ökonomen; Schätzung; EU-Staaten